OCCUPATIONAL ACCIDENTS WITH POTENTIALLY CONTAMINATED MATERIAL INVOLVING NURSING WORKERS - Gabriela da Cunha Januário; Priscila do Carmo Freitas de Carvalho; Graziele de Carvalho Lemos; Elucir Gir; Silmara Elaine Malaguti Toffano (Universidade Federal do Paraná, 2017)
The objective was to describe the occupational accidents involving biological material involving nursing team workers. Descriptive and retrospective study with a quantitative approach, undertaken at a hospital in the Central-West of the state of Minas Gerais. The data were collected by consulting the occupational accident reporting forms and histories, safeguarding all ethical aspects. Between October 2014 and May 2016, 61 workers were victims of 71 cases of exposure; 56 (91.8%) are women, 32 (52.5%) nursing technicians, 31 (50.8%) working in clinical nursing services. Percutaneous exposure 37(60.7%) during venipuncture 17(27.9%) was predominant. In conclusion, these cases of exposure could be avoided, which evidences the need for continuing education for these professionals and the implementation of devices with safety engineering.